“Black Ovaries”: An Uncommon Case of First Systemic Recurrence of Melanoma - Gerardo Cazzato; Anna Colagrande; Francesca Arezzo; Leonardo Resta; Giuseppe Ingravallo (Reports, 2021)
Here we describe a rare case of a 48-year-old woman with a previous history of malignant melanoma (pT2a pathological stage, IB clinical stage) occurring about five years previously. She complained of abdominal pain and pelvic discomfort, diagnosed as a consequence of a bilateral ovarian solid masses completely occupying the recto-uterine space. She underwent laparotomy surgery with total hysterectomy and bilateral salpingo-oophorectomy. Gross examination of the excised material revealed an unusual grey-black bilateral ovarian tumor; a histopathological diagnosis of ovarian bilateral metastatic melanoma was made. Imaging study (CT/MRI) did not reveal metastasis in other zones of the body. Melanoma metastasis usually affects the skin, liver, brain and lungs, and rarely gynecological localizations. On the other hand, most bilateral ovarian tumors are comprised of serous carcinoma, mature teratoma and gastrointestinal carcinoma metastasis. Exceptionally, primary ovarian melanoma may arise in mature ovarian cystic teratomas.